FRI0453 The Increased Prevalence of Nafld Is Worrisome among Patients with Psoriatic Arthritis. (15th July 2016) - Gaspari, C.; Carvalho, G.; Anjos, L.; Sampaio-Barros, P.; Moraes, J.; Gonçalves, C.; Saad, C.; Goldenstein-Schainberg, C.
Abstract : Background: Non-alcoholic fatty liver disease (NAFLD) affects 20–30% of general population and a wide range of 14–59% patients with cutaneous psoriasis (PsO). Psoriatic arthritis (PsA) has been linked to comorbidities including diabetes, arterial hypertension, dyslipidemia and metabolic syndrome (MetS) though data on NAFLD in PsA is lacking. In fact, in PsA, NAFLD has been evaluatedin only one Italian study affecting 28% patients. Objectives: To evaluate the prevalence of NAFLD in our cohort of patients with PsA. Methods: All patients with PsA regularly followed-up during a 6 month period at our outpatient rheumatology clinic were studied. They were evaluated byabdominal ultrasound (US) and NAFLD was defined in the presence of hepatic steatosis (US = Grades I to III).The occurrence of associated comorbidities, includingarterial hypertension, diabetes and dyslipidemia was recorded and the NCEP-ACT III criteria were applied to identify subjects with metabolic syndrome (MetS). DAS 28, BASDAI and ASDAS were used to assess PsA disease activity, while HAQ was performed to assess functional impairment. Student's t, Chi-square and Fisher's exact tests were performed for statistical analyses and P values ≤0.05 were considered significant. Results: Fifty six PsA patients were initially enrolled, but 3 were excluded due to the presence of alcoholic cirrhosis in 2 and a positive serology for hepatitis C in 1. Among the remaining 53 patients, 26 were males and 27 females, with mean age = 54, 8±13 yrs (27–76) and mean disease duration = 14, 4±8, 1 yrs (04–40). US revealed NAFLD in 33/53 (63%) patients with PsA, confirmed by liver biopsy in 2. Arterial hypertension, diabetes and dyslipidemia affected 81%, 42%, 75% of patients with NAFLD respectively (P<0.001). MetS was present in 58, 5% (31/53) individuals, significantly more prevalent in patients with compared to those without NAFLD: 26/33 (78.8%) vs. 05/20 (25.0%), P<0.001, despite of gender. All disease activity indices (% patients with DAS28>2.6), mean BASDAI and mean ASDAS) and HAQ scores were similar among patients with or without NAFLD (55.6% vs 46.7%; 3.1 vs 3.7; 1.9 vs 2.3; 1 vs 0.9 respectively, P>0.05). Conclusions: NAFLD is very common in our cohort of PsA patients occurring in over 2/3 regardless of disease activity and associated to MetS in most subjects, suggesting a relationship between these conditions. Moreover, screening for NAFLD inPsA patients is warranted in order to avoid increased overall liver morbidity. References: Psoriatic arthritis: a systematic review, International Journal of Rheumatic Diseases 2010; 13: 300–317. Wenck et al. Journal of the European Academy of Dermatology, 2011. Candia et al. Journal of the European Academy of Dermatology, 2015. Di Minno et al. Arthritis Research & Therapy, 2012. Disclosure of Interest: None declared